Bab el Shams: "It Is Impossible to Write a Novel" - Rimmon-Kenan, Shlomith (MiKAN, 2017)
Bab el Shams is a performative novel, which gives the reader an experience of suffering that is analogous, to some extent, to that of its characters. This essay discusses a response combining a nightmarish experience with the incapacity to let go. It traces this experience back to several characteristics of Khoury’s novel: its meta-fictional and citational nature; the ambivalent relations between the narrator and his comatose narratee; the tension between coherence and fragmentation, the latter both challenging a hegemonic narrative and giving rise to a plurality of stories that often contradict each other and underscore the inaccessibility of truth; the blurring of the boundaries between reality and fairytale or hallucination; and last but not least, the horror of the represented events and the feelings of guilt they provoke in the implied Israeli reader. The essay ends by comparing the complex effect of Bab el Shams to the Western literary tradition where the challenge to narrative is both threatening and liberating, such as in the works of Beckett and Genet.